Micromelic Pseudoachondroplasia Simulating Rickets in a 9-Year-Old Boy - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Pseudoachondroplastic dysplasia is a rare inherited disorder characterized by skeletal malformations resulting to short stature. These individuals are usually normal at birth but due to the abnormal skeletal growth or dysplasia, the skeleton becomes weakened and malformed. The skeletal deformities increase as the individual grows and gains weight. Affected individuals may have radiographic features simulating vitamin D deficiency. In addition, affected individuals may have spinal abnormalities including abnormally increased lumbar lordosis and kyphosis. This case is being presented because of its rarity and simulation of rickets in the growing young child.